An Institutional/Organizational Turn: Getting to Work–Life Quality and Gender Equality. (May 2015) - Moen, Phyllis
This review essay examines three recent books contributing toward a broader reframing of approaches to and scholarship on the work–family–gender interface. They are part of an institutional/organizational turn, focusing explicitly on public and organizational policies and practices that constrain or facilitate both gender equality and work–life quality. This moves beyond microlevel studies of individuals and families to link and situate gender inequality, stress, and work–family conundrums in outdated state and organizational policy regimes, norms, and expectations that can be challenged and changed.